Witchcraft in Russia and Ukraine, 1000–1900 - Kivelson, Valerie A.,Worobec, Christine D. (Cornell University Press, 2020)
This sourcebook provides the first systematic overview of witchcraft laws and trials in Russia and Ukraine from medieval times to the late nineteenth century. Witchcraft in Russia and Ukraine weaves scholarly commentary with never before published primary source materials translated from Polish, Russian, and Ukrainian. These sources include the earliest references to witchcraft and sorcery, secular and religious laws regarding witchcraft and possession, full trial transcripts, and a wealth of magical spells. The documents present a rich panorama of daily life and reveal the extraordinary power of magical words. Editors Valerie A. Kivelson and Christine D. Worobec present new analyses of the workings and evolution of legal systems, the interplay and tensions between church and state, and the prosaic concerns of the women and men involved in witchcraft proceedings. The extended documentary commentaries also explore the shifting boundaries and fraught political relations between Russia and Ukraine.
10.1515/9781501750670
Keywords: Aufsatzsammlung; Hexenprozess; Hexerei; Recht